Hepatitis From Spiroplasma sp. in an Immunocompromised Patient. Issue 9 (1st April 2015) - Mueller, N. J.; Tini, G. M.; Weber, A.; Gaspert, A.; Husmann, L.; Bloemberg, G.; Boehler, A.; Benden, C.
<x xml:space="preserve">Abstract</x> A 70‐year‐old lung transplant recipient patient was admitted with fever, nausea, abdominal pain, peripheral edema and pronounced weakness. An initial work‐up for presumed infection revealed cholestatic hepatitis, leukocytosis and thrombocytopenia, but failed to detect a pathogen. An increased glucose uptake exclusively in the liver was demonstrated by positron emission tomography. Liver biopsy showed basophilic inclusions in the cytoplasm of hepatocytes. Broad‐ range 16S rRNA gene PCR followed by sequence analysis yielded Spiroplasma sp. in two independent blood samples and the liver biopsy, confirming Spiroplasma sp. as the causative agent. Antibiotic treatment with doxycycline and azithromycin led to complete recovery.